The transfer of ICT training to the workplace. - Justin Eaglen (2007)
"This thesis examines the extent to which Information and Communication Technology (ICT) training is transferred to the workplace and how ICT training impacts on company performance with training transfer being defined as "the extent to which skills acquired in a training program are applied, generalised, and maintained over some time in the job environment" (Baldwin and Ford, 1988) The thesis begins with an introduction to the subject area, including the money the European Union and the Welsh Assembly Government have invested in attempting to increase the provision of SME ICT training in Wales. A review of the relevant literature was conducted, and whilst a fair amount was found in the area of technology acceptance, training effectiveness and general training transfer, it was found lacking in the area of ICT training. A detailed survey concerned with some of the salient issues related to the transfer of ICT training to the workplace was carried out with employees and employers of small and medium sized enterprises (SMEs) in South Wales. In addition, a number of small case studies with were also conducted. The resulting data from the analysis showed a number of findings, including: that training transfer is not necessarily related to post-training usage, training is more beneficial (in terms of transfer) for employees who had little previous experience than those who had more experience, and older employees do not benefit from training as much as younger employees. The resulting information can be used by the stake holders involved in the training transfer process, namely funding agencies, training providers, employers and employees, to improve the transfer of training to the workplace and the impact this has on company performance."